Effect of didecyl dimethyl ammonium chloride-impregnated washcloth wipe whole-body bathing on catheter-related blood stream infections and central venous line-associated infections in adult intensive care units - Dehn, Fabian von; Mutters, Nico T.; Eichel, Vanessa; Merle, Uta; Brenner, Thorsten; Nafe, Michael; Sander, Anja; Wolkewitz, Martin; Frank, Uwe (Clinical microbiology and infection, 2022)
Objective - To investigate the effect of daily whole-body bathing (WBB) using disposable washcloth wipes/caps impregnated with an antiseptic solution containing the quaternary ammonium base compound didecyl dimethyl ammonium chloride (DDAC). - Methods - A prospective double-blind randomized crossover trial was conducted to compare WBB of adult intensive care unit (ICU) patients with washcloth wipes/caps impregnated with either regular cleanser/shampoo or the antiseptic DDAC. The clinical trial was performed in a medical ICU (MICU) and a surgical ICU (SICU). The study period was divided into two 6-month intervals with alternating treatment regimens. - Results - A total of 1540 ICU patients (total length of ICU stay 10 470 days) were included in the trial. Compared to controls, DDAC bathing was found to be associated with reduced incidence rates per 1000 patient days for central-venous-line-associated infections (CLAIs) caused by Gram-positive bacteria (GPB) from 16.39 (95%CI 13.1-20.3) in the control group to 7.28 (95%CI 5.2-9.9) in the intervention group (p 0.01). A stratified analysis by unit showed that the incidence rates of CLAI due to GPB were reduced by the intervention in both the MICU and the SICU from 21.2 (95%CI 15.8-27.7) to 9.3 (95%CI 5.8-14.1) (p < 0.01) and from 12.1 (95%CI 8.3-17.0) to 5.7 (95%CI 3.4-9.1) (p 0.01), respectively. There was a trend towards reduction in catheter-related bloodstream infections (CRBSIs) and bloodstream infections (BSIs); however, this did not reach statistical significance due to carry-over effects and small numbers. - Conclusions - Given the growing need for new concepts to prevent and control healthcare-associated infections, DDAC may be a new and promising agent for WBB of ICU patients.